Maṭla‘ Anak Bulan Menurut Perspektif Fiqh: (Maṭla‘ al-Hilal From Islamic Jurisprudence Perspective) - Hashim, Muhammad Ridzuan; Man, Saadan; Mohd Nawawi, Mohd Saiful Anwar (Online Journal of Research in Islamic Studies, 2024)
Maṭla’ in observing the moon crescent is an important process in determining the beginning of the Hijri month in Islam. From a fiqh perspective, the maṭla’ of the moon is a significant issue that affects the Islamic calendar, especially in setting important dates such as the beginning of Ramadan and Hari Raya. The process of maṭla’ involves thoroughly observing the moon’s crescent to determine its visibility. This is typically done by experienced individuals who are knowledgeable about astronomy and the lunar cycle. They look for the first sighting of the crescent after the new moon, using specialized equipment or even with the naked eye with relevant criteria. The accuracy of this observation is crucial in determining the beginning of the Hijri month and the corresponding Islamic events. To determine the beginning of the Hijri month accurately, scholars form certain methods based on fiqh rules to identify the maṭla’ of the moon. Different schools of jurisprudence have different opinions about the determination of the maṭla’ of the moon, including the criteria for understanding relevant hadiths. A textual analysis has been done in this study to ensure consistency and accuracy in setting the beginning of Hijri month for matters of worship and celebration in Islam.